Dinâmica metabólica em Piper gaudichaudianum: estudo das etapas de ciclização estereosseletiva do ácido gaudichaudianico - Carvalho, Amanda Uliana de [UNESP] (2014)
The Piperaceae family comprises about 4000 species, and the genus Piper is the most abundant. Many species of this genus are used in folk medicine to treat various diseases. The wide biological potential of this family is due to the accumulation of different classes of secondary metabolites, among which stand out the prenylated derivatives of p-hydroxybenzoic acid and its cyclized products, known as chromenes and/or chromanes, which are characterized by the presence of a pyran ring fused with a benzene moieity. Piper gaudichaudianum, in particular, presents in its constitution the 2-methyl -2-(4'-methyl-3'-pentenyl)-8-(3''-methyl-2-butenyl)-2H-1-chromene-6-carboxylic acid, known as gaudichaudianic acid, a prenylated chromene that is the major metabolite in leaves and roots of this species. This compound has shown trypanocidal and antifungal activities. Chemical studies demonstrated the presence of two naturally occurring rare isomeric forms, (+)-S and (-)-R, gaudichaudianic acid, arousing the interest in further evaluations of their biosynthetic steps. Therefore, the present work aimed to study the biosynthetic pathway related to the cyclization step leading to the enantiomers of gaudichaudianic acid using prenylated benzoic acid derivatives as intermediates. The proposed chemical and enzymatic cyclizations were evaluated using as the precursor the 3-geranyl-4-hydroxy-5-(3'-methyl-2'-butenyl )benzoic acid, known as myrsinoic acid identified and isolated from P. gaudichaudianum. To evaluate the possibility of cyclization occur by chemical methods acidic media and heating conditions were used. Under these conditions the formation of gaudichaudianic acid was not observed, which shows that the cyclization may occur enzymatically, catalyzed by a cyclase-type enzyme. Enzyme assays were performed using soluble and microsomal fractions obtained from the leaves P. gaudichaudianum and using the 3-geranyl-4-hydroxy-5-(3'-methyl-2'-butenyl) benzoic...